On nonlinear perturbations of the Schrödinger equation with discontinuous coefficients - Jäger, Willi; Simon, László (Acta mathematica hungarica, 2003)
The results of [2] by W. Jäger and Y. Saito on the Schrödinger equation with discontinuous coefficients are extended to nonlinear perturbations of the equation.